The molecular components of the anti-inflammatory cholinergic pathway are extrasplenic - Warda Merchant; Steven Wyler; Bandy Chen; Laurent Gautron (PLoS ONE, 2025)
The anti-inflammatory cholinergic pathway describes the interaction between cholinergic vagal nerves and splenic immune cells, yet the exact mechanisms underlying the anti-inflammatory cholinergic pathway remain disputed. Here, we mapped the expression of key molecular components of the anti-inflammatory cholinergic pathway in the adult mouse using RNAScope in situ hybridization (ISH) and quantitative PCR (qPCR). In C57BL/6J wild-type male mice, we observed the expression of choline acetyltransferase (Chat) and alpha 7 nicotinic acetylcholine receptor (Chrna7) in various autonomic neurons throughout the body, but not in the spleen, even after bacterial lipopolysaccharide (LPS) treatment. In contrast, the beta-2 adrenergic receptor (Adrb2), another autonomic receptor with well-documented anti-inflammatory actions, was highly expressed in the spleen, with a significant decrease following LPS administration. Interestingly, Adrb2 was also expressed at lower levels in the spleen of a newly generated global knockout mouse for Chrna7. Lastly, we did not observe YFP-positive cells or axons in the spleen of the ChAT-Cre-ChR2-YFP mouse. Based on our findings, we propose a new model of the cholinergic anti-inflammatory pathway that highlights the roles of extrasplenic cholinergic signaling.